Implementasi Wakaf Uang dalam Upaya Pemberdayaan Masyarakat (Studi PKPU Provinsi Jawa Tengah) (TAWAZUN: Journal of Sharia Economic Law, 2022)
This paper aims to examine waqf in the form of developing social, economic and cultural activities in Islamic society. As is known, waqf should be managed properly, so that the results can be used for the benefit of society. This study uses a sociological juridical approach, with the type of analytic descriptive research. The data collection method uses primary and secondary data. Primary data is obtained from direct interviews with respondents, while secondary data is obtained from laws and regulations, library books relevant to the object of research. The results of this study indicate that; 1) Implementation of cash waqf in PKPU Central Java through several programs, namely: CBDRM (Community Based Distater Risk Management), BUDARZI (Nutrition Aware Mother), Healthy Community, Green Community, PROSPECT (Economic Empowerment Synergy Program), Community Potential Based Education Program, and Orphan Vouchers. 2) Constraints or obstacles in the implementation of cash waqf, which are not yet supported by adequate regulations, weak public literacy regarding cash waqf, and found many nadzhirs who still have traditional understanding.